The Analysis of Exports Performance in Algeria for the Period 1992-2016 - Traore, Mohamed Moussa; Saqfalhait, Nahil Ismail (International Journal of Economics and Financial Issues, 2019)
The study aims to investigate the export performance in Algeria. For this purpose, the researcher used a descriptive approach to examine how trends in exports, export composition, export concentration, market share, and export volatility have changed in Algeria's plans and reform programs. The study found an improvement in Algeria exports during 1992-2016, but this performance weakened during the more recent years. The export composition showed that consumer products and raw materials represented the bulk of Algeria's total exports with an average share of 91.5%. The share of intermediate and capital goods was low, with a percentage of only 3%. It also showed that the largest part of Algeria's products was exported to Europe and Central Asian and North American countries, with an average share of 86%. The results revealed a lack of diversification in Algeria's exports as the product concentration was on average, 97.2%. The extent of geographic concentration ranged between 61% and 78% in Algeria's exports was also high. The market share of Algeria has improved considerably during the study period as it achieved the highest value in 2011. This expansion is explained by the high integration of Algeria by exporting fuel products in the world market. The extent of export volatility has varied during the study period as it was at its highest level (54.1%) during the period 1992-1995. In contrast, the extent of Algeria's exports was less during 2009-2013 as it was only 19.8%. To improve export performance in Algeria, the government should reduce the concentration in their export products and upgrade the structure of their export basket by including more advanced products (such as intermediate, capital and other manufactured products). Improving the export performance in Algeria can also be achieved by enhancing trade relationships with traditional markets as well as other trading partners. These initiatives can be also helpful in reducing the extent of volatility in Algeria's export earnings. Keywords: Exports Composition, Exports concentration, Market share, Export volatility. JEL Classifications: F100 DOI: https://doi.org/10.32479/ijefi.8447